Performance evaluation of chemical, biological and physical indicators in the process of sterilization under the effect of non-condensable gases. (February 2021) - Rodrigues, S.B.; de Souza, R.Q.; Graziano, K.U.; Erzinger, G.S.; Souza, O.
Summary: Background: The risk concerning the presence of non-condensable gases (NCGs) has already been demonstrated, but routine monitoring still requires further research to be implemented in each sterilization cycle. Aim: Performance evaluation of the physical, chemical and biological indicators used in monitoring in comparison with a sterilizer integrated detector for NCG in the Sterilization Process. Methods: Chemical indicators (type 2 Bowie–Dick test, type 5 and type 6 models), self-contained biological indicators and physical indicators (temperature, pressure, thermal qualification and a patented integrated air detector) were used to monitor the steam sterilization process in two situations of controlled failure: chamber leakage and door seal failure. This controlled failure was obtained by the presence of a known amount of air: 0–30 L/min for chamber leakage and 0–30% for the door seal failure. Evaluation tests were carried out with and without the use of process challenge devices (PCDs). Findings: In both studies, the Bowie-Dick Test showed different results, according to the manufacturer. The biological, physical or chemical indicators without a PCD were unable to detect small volumes of NCGs in both simulations. Conclusion: The integrated air detector can be considered an option for the detection of NCGs in each cycle.